2018
DOI: 10.1093/jhps/hny024
|View full text |Cite
|
Sign up to set email alerts
|

Quadratus lumborum block provides improved immediate postoperative analgesia and decreased opioid use compared with a multimodal pain regimen following hip arthroscopy

Abstract: The purpose of our study was to evaluate the effect on immediate patient outcomes following hip arthroscopy with use of a preoperative, single shot quadratus lumborum (QL) block. We retrospectively reviewed patients who underwent hip arthroscopy following a preoperative QL block. These patients were matched by age and gender to patients who had not received a block. Visual analogue scale (VAS) pain scores immediately postoperatively and at the time of discharge were recorded. Hourly and overall opioid intake i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…Quadratus lumborum block is an emerging technique for peripheral nerve blockade, which generates an analgesic effect by unilaterally blocking spinal nerves from T6-T9 to L1-L3 [9] Considering its wide block range, It has been increasingly used for postoperative analgesia in patients undergoing middle and lower abdominal and hip surgery [10][11][12], and showed satisfactory results no matter in single injection mode or continuous infusion mode. However, application of continuous QL block for upper abdominal pain is less well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Quadratus lumborum block is an emerging technique for peripheral nerve blockade, which generates an analgesic effect by unilaterally blocking spinal nerves from T6-T9 to L1-L3 [9] Considering its wide block range, It has been increasingly used for postoperative analgesia in patients undergoing middle and lower abdominal and hip surgery [10][11][12], and showed satisfactory results no matter in single injection mode or continuous infusion mode. However, application of continuous QL block for upper abdominal pain is less well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound-guided QLB technique was first described by Blanco [11,12], and the benefits of QLB for postoperative pain relief and opioids-sparing effect have been reported by several randomized controlled trials and case reports [2,5,6,[8][9][10][19][20][21][22][23][24][25][26][27][28][29][30]. All approaches have been proved the synergistic efficacy for multimode analgesia, especially for QLB2 or QLB3 after laparoscopic surgery, cesarean section and total hip arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has an effect on visceral pain and abdominal incision pain. Additional studies [7,12,31] have shown that two different trunk blocks have adequate analgesic effects for the management of pain after abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%